Clinical outcomes after anterior cruciate ligament injury: Panther Symposium ACL Injury Clinical Outcomes Consensus Group. Issue 5 (22nd July 2020) - Svantesson, Eleonor; Hamrin Senorski, Eric; Webster, Kate E; Karlsson, Jón; Diermeier, Theresa; Rothrauff, Benjamin B; Meredith, Sean J; Rauer, Thomas; Irrgang, James J; Spindler, Kurt P; Ma, C Benjamin; Musahl, Volker
Abstract : Purpose: A stringent outcome assessment is a key aspect for establishing evidence-based clinical guidelines for anterior cruciate ligament (ACL) injury treatment. The aim of this consensus statement was to establish what data should be reported when conducting an ACL outcome study, what specific outcome measurements should be used and at what follow-up time those outcomes should be assessed. Methods: To establish a standardised assessment of clinical outcome after ACL treatment, a consensus meeting including a multidisciplinary group of ACL experts was held at the ACL Consensus Meeting Panther Symposium, Pittsburgh, PA, USA, in June 2019. The group reached consensus on nine statements by using a modified Delphi method. Results: In general, outcomes after ACL treatment can be divided into four robust categories—early adverse events, patient-reported outcomes, ACL graft failure/recurrent ligament disruption, and clinical measures of knee function and structure. A comprehensive assessment following ACL treatment should aim to provide a complete overview of the treatment result, optimally including the various aspects of outcome categories. For most research questions, a minimum follow-up of 2 years with an optimal follow-up rate of 80% is necessary to achieve a comprehensive assessment. This should include clinical examination, any sustained re-injuries, validated knee-specific patient-reported outcomes and Health-Related Quality of Life questionnaires. In the mid-term to long-term follow-up, the presence of osteoarthritis should be evaluated. Conclusion: This consensus paper provides practical guidelines for how the aforementioned entities of outcomes should be reported and suggests the preferred tools for a reliable and valid assessment of outcome after ACL treatment. Level of Evidence: Level V.